Identification and characterization of porcine Rotavirus A in Chilean swine population - Neira, Victor; Melgarejo, Cristián; Urzúa-Encina, Constanza; Berrios, Felipe; Valdes, Valentina; Mor, Sunil; Brito-Rodriguez, Barbara; Ramirez-Toloza, Galia Andrea (Frontiers in Veterinary Science, 2023)
Rotavirus A (RVA) is a common cause of diarrhea in newborn pigs, leading to significant economic losses. RVA is considered a major public health concern due to genetic evolution, high prevalence, and pathogenicity in humans and animals. The objective of this study was to identify and characterize RVA in swine farms in Chile. A total of 154 samples (86 oral fluids and 68 fecal samples) were collected, from 22 swine farms. 58 (38%) samples belonging to 14 farms were found positive for RVA by real-time RT-PCR. The samples with low Ct values (21) and the two isolates were selected for whole genome sequencing. Nearly complete genomes were assembled from both isolates and partial genomes were assembled from five clinical samples. BLAST analysis confirmed that these sequences are related to human and swine-origin RVA. The genomic constellation was G5/G3-P[7]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Phylogenetic analysis showed that VP4, VP1, VP2, NSP2, NSP3, NSP4, and NSP5 sequences were grouped in monophyletic clusters, suggesting a single introduction. The phylogenies for VP7, VP6, VP3, and NSP1 indicated two different origins of the Chilean sequences. The phylogenetic trees showed that most of the Chilean RVA sequences are closely related to human and swine-origin RVA detected across the world. The results highlight the potential zoonotic nature of RVA circulating in Chilean swine farms. Therefore, it is important to continue RVA whole genome sequencing globally to fully understand its complex epidemiology and early detection and characterization of zoonotic strains.